World experience in the use of spore-forming bacilli for the treatment and prevention of food allergy in children - L.S. Ovcharenko; A.A. Vertegel; T.G. Andrienko; I.V. Samokhin; A.V. Kryazhev; D.N. Sheludko; Т.В. Slutskaya (Zaslavsky O.Yu., 2017)
The article presents a review of the literature on current clinical and experimental studies on the use of spore-forming Bacillus subtilis and Bacillus licheniformis for the treatment and prevention of food allergies in children. Numerous proofs of the correlation between disorders in the composition of the intestinal microflora of children and various allergic diseases in the first years of life are presented. It has been shown that probiotics containing Bacillus subtilis and Bacillus licheniformis exert a complex direct and indirect positive impact on the prevention of allergic disorders. They can temporarily change the composition of the intestinal microbiota and potentially reduce the susceptibility of the host organism to allergies. Such approaches are promising and do not violate the natural physiological mechanisms of development of age-related immune tolerance to various antigens, which prevents the formation of food allergies in children.